An Investigation into Reliable Transport Limits and Slip Velocity for Fluidized Dense Phase Conveying of Cement - Srivastava, Gaurav Prakash (My University, 2015)
This report presents the results of an investigation into the minimum transport boundary of pneumatic conveying of cement and calculation of the slip velocity for pneumatic conveying of fly ash and cement. The properties of conveying materials used in experiments of this report are: cement (median particle diameter: 19 µm; particle density: 2910 kg/m^3; bulk density: 1080 kg/m^3) and fly ash (median particle diameter: 45 µm; particle density: 1950 kg/m^3; bulk density: 950 kg/m^3). These materials were conveyed through four different pipelines (viz. 43 mm I. D. × 24 m length, 54 mm I. D. × 24 m length, 54 mm I. D. × 70 m length and 69 mm I. D. × 24 m length) over the wide range of flow conditions (from fluidized dense phase to dilute phase flow). Pneumatic conveying characteristics based on total pipeline pressure drop were developed for all the pipelines. To define the safe, reliable transport limits for cement Froude number based criteria were used at pipe inlet (Fri = 5 to 10). These limits are compared with one of the most popular model Mallick and Wypych (2010). For slip velocity, an investigation has been done for both fly ash and cement. A high resolution digital signal reflex camera is installed on a tripod to observe a detailed flow of material at a certain position of the sight glass section. The camera is capable to take video at 50 to 60 frames per second. These produced frames are further analyzed to estimate the slip velocity.
ME, MED
Keywords: bulk solids; minimum transport; fluidized dense phase; pneumatic conveying; slip velocity; MED